Indigenizing the Classroom: Engaging Native American/First Nations Literature and Culture in Non-native Settings (2021)
In the past four decades Native American/First Nations Literature has emerged as a literary and academic field and it is now read, taught, and theorized in many educational settings outside the United States and Canada. Native American and First Nations authors have also broadened their themes and readership by exploring transnational contexts and foreign realities, and through translation into major and minor languages, thus establishing creative networks with other literary communities around the world. However, when their texts are taught abroad, the perpetuation of Indian stereotypes, mystifications, and misconceptions is still a major issue that non-Native readers, students, and teachers continue to struggle with. To counter such distorted representations and neo/colonialist readings, this book presents a strategic selection of critical case studies that set specific texts within cross-cultural contexts wherein Native-based methodologies and key concepts are placed at the center of the reading practice. The challenging role of teachers and researchers as potential intermediaries and responsible disseminators of what Gayatri C. Spivak calls “transnational literacy” as well as the reception of Native North American works, contexts, and themes by international readers thus becomes a primary focus of attention. This volume provides a set of critical analyses and practical resources that may enable teachers outside the United States and Canada to incorporate Native American/First Nations literature and related cultural and historical texts into their teaching practices and current research interests in a creative, decolonizing, and responsible manner.En las últimas cuatro décadas, la literatura nativa americana y de las primeras naciones ha surgido como campo literario y académico, y ahora se lee, enseña y teoriza en muchos entornos educativos fuera de Estados Unidos y Canadá. Los autores de textos nativos americanos y de las primeras naciones también han ampliado sus temas y sus lectores, explorando contextos transnacionales y realidades extranjeras, y, mediante la traducción a lenguas principales y secundarias, han establecido redes creativas con otras comunidades literarias de todo el mundo. Sin embargo, cuando sus textos se enseñan en el extranjero, la perpetuación de los estereotipos, las mistificaciones y los conceptos erróneos sobre los indios siguen siendo un problema importante con el que se enfrentan los lectores, estudiantes y profesores no nativos. Para contrarrestar tales representaciones distorsionadas y lecturas neocolonialistas, este libro presenta una selección indispensable de estudios críticos que ubican textos específicos dentro de contextos interculturales en los que las metodologías basadas en los nativos y los conceptos clave se sitúan en el centro de la práctica de la lectura. El difícil papel de los profesores e investigadores como posibles intermediarios y difusores responsables de lo que Gayatri C. Spivak denomina “alfabetización transnacional”, así como la recepción de las obras, contextos y temas de los nativos norteamericanos por parte de los lectores internacionales, se convierten así en un foco de atención primordial. Este volumen ofrece un conjunto de análisis críticos y recursos prácticos que facilitan a los profesores de fuera de Estados Unidos y Canadá incorporar la literatura nativa norteamericana y de las primeras naciones, así como los textos culturales e históricos conexos a sus prácticas docentes y a sus intereses actuales de investigación, de manera creativa, descolonizadora y responsable.
Keywords: literatura nativa americana; estudios críticos